Hermite–Hadamard-Type Integral Inequalities for Functions Whose First Derivatives are Convex - Feng Qi; Tian-Yu Zhang; Bo-Yan Xi (Український математичний журнал, 2015)
We establish some new Hermite–Hadamard-type inequalities for functions whose first derivatives are of convexity and apply these inequalities to construct inequalities for special means. Встановлено дєякі нові нєрівності типу Ерміта - Адамара для Функцій, похідні яких мають опуклість. Ці нєрівності застосовано при побудові нерівностей для спеціальних середніх.